2021
DOI: 10.1021/acsomega.1c02956
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Pickering Emulsified Polymeric Gel System as a Water Blocking Agent

Abstract: The conventional methods for controlling excess water production in oil/gas wells can be classified on the basis of the mechanism (pore-blocking mechanism and relative permeability modification) used. Gel systems developed on the basis of a pore-blocking mechanism completely block the pores and stop the flow of both oil and water, whereas a relative permeability modifier (RPM) only restricts the flow of a single phase of the fluid. The gel working on the basis of the pore-blocking mechanism is known as a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In contrast, oil relative permeability remained unaffected. The ndings align with those observed during core ooding experiments conducted using the same Pickering emulsi ed gel system (Saikia et al, 2021) (Saikia et al, 2019), suggesting that the originally postulated conformance control mechanism only partially holds. While the hypothesis of emulsion separation and aqueous phase gelling was con rmed, the Thin Film mechanism was debunked.…”
Section: Conformance Control Mechanism In Glass Micromodel IIsupporting
confidence: 78%
See 3 more Smart Citations
“…In contrast, oil relative permeability remained unaffected. The ndings align with those observed during core ooding experiments conducted using the same Pickering emulsi ed gel system (Saikia et al, 2021) (Saikia et al, 2019), suggesting that the originally postulated conformance control mechanism only partially holds. While the hypothesis of emulsion separation and aqueous phase gelling was con rmed, the Thin Film mechanism was debunked.…”
Section: Conformance Control Mechanism In Glass Micromodel IIsupporting
confidence: 78%
“…This temperature exposure spanned a duration of 24 hours. The inherent design of the Pickering emulsi ed gel system ensured that, during this period, the emulsion would undergo phase separation, resulting in the formation of distinct aqueous and oleic phases (Saikia et al, 2021(Saikia et al, , 2019. The aqueous phase subsequently underwent a transformation into a rigid gel structure, serving as a formidable impediment to the ow of the formation water.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The technique was used to seal a 109 m long channeling period by perforating the casing, blocking the agent prior to channeling, and implementing the sealing channeling homework. The results showed that the sealing effect was good, and no crossflow occurred between the two layers even after 2 years, demonstrating the technical superiority of the method. , An annulus cement sheath microcrack sealing fluid should have the following characteristics to demonstrate a good performance: (1) it must have good ability to enter the cement sheath microcrack; (2) in the case of dynamic interzonal channeling, the blocking fluid needs to have good retention capacity in the cement sheath microcrack to prevent displacement of the annulus channeling fluid to the low-pressure formation; and (3) the blocking liquid needs to have enough blocking capacity and life after gelling and solidification to ensure the blocking effect. To ensure that the sealing fluid is easy to enter the cement sheath microcrack, the viscosity of the polymer aqueous solution is generally designed to be low, only about 1 mPa·s.…”
Section: Introductionmentioning
confidence: 99%